Process for recovering gold from waste printed circuit boards

CN122941890APending Publication Date: 2026-10-20KUSN HUISHENG INDAL
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202610807679.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,该方法采用单一氧化剂直接处理,未涉及分级选择性处理策略,且未公开氧化还原电位的在线反馈调控机制

Benefits of technology

(1)多级选择性氧化预处理技术实现了贱金属与金的高选择性分离:一级稀硫酸预浸处理通过控制硫酸浓度和液固比,主要去除混合粉末中含量较高的铜、锌等活泼贱金属,避免了直接进行硫脲浸出时贱金属对金浸出的竞争干扰;二级三价铁选择性氧化处理利用Fe3+/Fe2+标准电极电位介于贱金属和金之间的特点,以银/氯化银电极为参比电极实时监测氧化还原电位,通过ORP传感器的实时反馈调节三价铁的补充速率,将氧化还原电位稳定控制在300~500 mV范围内,使Fe3+选择性地将残余的铜、镍等贱金属氧化溶解,而金因电极电位远高于Fe3+而完整保留在固体残渣中。通过一级预浸和二级选择性氧化的协同配合,贱金属的总去除率可达95%以上,为后续高效吸附回收创造了极为有利的条件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1780540079452-000002
    Figure REF-OBJ-1780540079452-000002
  • Figure REF-OBJ-1780540079452-000003
    Figure REF-OBJ-1780540079452-000003
  • Figure REF-OBJ-1780540079452-000004
    Figure REF-OBJ-1780540079452-000004
Patent Text Reader

Abstract

This invention discloses a gold recovery process from waste circuit boards, comprising a multi-stage selective oxidation pretreatment. A first-stage dilute sulfuric acid pre-leaching removes most base metals, followed by a second-stage selective oxidation treatment with trivalent iron. An ORP sensor, using a silver / silver chloride electrode as a reference electrode, monitors the redox potential in real time to achieve precise separation of base metals and gold. Acidic thiourea complexation leaching is then performed, with continuous monitoring and replenishment of thiourea during the leaching process to maintain a stable concentration. Graphene provides π electrons for specific interactions with gold, chitosan provides chelating coordination sites, and mesoporous silica provides high specific surface area mass transfer channels. Ultrasonic-assisted pulsed electrodeposition is then performed, applying an ultrasonic field during deposition and combining it with pre-electrolysis to remove base metal impurities. Waste liquid is then classified and recycled, recovering valuable metals and achieving water recycling. This invention achieves a total gold recovery rate of no less than 80% and a sponge gold purity of no less than 99.5% through multi-feature synergy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic waste resource recycling technology, specifically a gold recycling process for waste circuit boards. Background Technology

[0002] With the widespread use of electronic products and the rapid pace of upgrades, the amount of waste electronic and electrical products (electronic waste) has increased dramatically. Waste circuit boards are an important component of electronic waste. The gold content in each ton of waste circuit boards can reach 50 to 300 grams, which is far higher than the average content of natural gold ore (about 5 grams per ton). Therefore, waste circuit boards are called "urban mines" and have extremely high resource recycling value.

[0003] Currently, methods for recovering gold from waste circuit boards mainly fall into three categories: pyrometallurgy, hydrometallurgy, and biometallurgy. Pyrometallurgy removes organic components through high-temperature incineration, followed by refining of the metal concentrate, but it suffers from the emission of toxic gases such as dioxins. Traditional hydrometallurgy typically uses cyanidation, aqua regia, or thiourea leaching to directly treat waste circuit boards. While cyanidation offers high leaching efficiency, cyanide is highly toxic, posing serious threats to the environment and human health; aqua regia uses highly corrosive acids, causing severe equipment corrosion and incurring high wastewater treatment costs; and the thiourea leaching method often fails to achieve ideal gold leaching rates due to competitive reactions from base metal impurities.

[0004] Regarding selective pretreatment, Chinese patent CN107841630B discloses a method for separating noble and base metals in circuit boards. This method involves selective leaching by controlling the oxidation-reduction potential to 380-420 mV, dissolving the base metals while retaining the gold in the slag. However, this method uses a single oxidant for direct treatment, does not involve a graded selective treatment strategy, and does not disclose an online feedback control mechanism for the oxidation-reduction potential. Chinese patent CN119265418A discloses a method for preferentially stripping the gold plating layer from waste circuit boards using a controlled-potential etching method. This method employs ultrasonic enhancement and potential control, but it targets the stripping of the gold plating layer rather than the comprehensive treatment of waste circuit boards.

[0005] Existing technologies also have significant shortcomings in the gold separation and enrichment process. Traditional activated carbon adsorption methods have limited adsorption capacity for gold ions (typically 50-100 mg / g) and low selectivity, easily adsorbing competing metal ions such as copper and nickel, leading to reduced gold product purity. Chinese patent CN105622960B discloses a method for preparing a carboxymethyl chitosan / graphene oxide composite hydrogel, but this material is mainly used for electroplating wastewater treatment and does not address the selective adsorption of gold ions. Chinese patent CN112473630A discloses a composite graphene-chitosan aerogel for adsorbing hexavalent chromium ions; Chinese patent CN121103267A discloses an aminothiourea-reduced graphene oxide / chitosan composite aerogel for gold adsorption, but it does not involve the introduction of mesoporous silica or its three-dimensional porous structure design. Furthermore, gold deposits obtained by traditional direct current electrodeposition methods are often not dense and uniform enough, affecting the purity and quality of the gold product.

[0006] The stability of thiourea is a key issue during the leaching process. Thiourea in Fe... 3+ Oxidation easily leads to the decomposition of thiourea into products such as dimethylaminodithioformamide, resulting in increased thiourea consumption and decreased leaching efficiency. In the prior art, US Patent 20070272055 discloses a method for controlling the electro-oxidation of thiourea, which improves the leaching efficiency of gold by forming formamidinium disulfide as an oxidant, but it does not address online thiourea concentration monitoring and automatic replenishment mechanisms.

[0007] Existing technologies suffer from significant environmental pollution, low gold leaching rates, poor separation and enrichment efficiency, unstable product quality, and low resource utilization. There is an urgent need to develop a new process for recycling gold from waste circuit boards that is environmentally friendly, highly selective, efficient, and controllable. Summary of the Invention

[0008] The purpose of this invention is to provide a method for selectively recovering gold from waste circuit boards. This method achieves selective separation of base metals and gold through multi-stage selective oxidation pretreatment, stable control of the leaching process through an online monitoring and control system, efficient adsorption and enrichment of gold ions through functionalized graphene / chitosan / mesoporous silica three-dimensional porous composite aerogel, high-purity sponge gold products through ultrasonic-assisted pulse electrodeposition technology, and green and clean production through waste liquid classification and recycling.

[0009] To achieve the above objectives, the present invention provides the following technical solution: The technical solution provided by this invention is: a gold recycling process from waste circuit boards, comprising the following steps: S1. Multi-stage selective oxidation pretreatment: The waste circuit board is de-surfaced with plastic packaging and impurities, crushed under inert gas protection, and iron powder is removed by magnetic separation. The mixture is then screened by vibration to obtain a gold-enriched mixed powder. The mixed powder is first subjected to a first-stage dilute sulfuric acid pre-immersion treatment to remove most of the base metals, and then subjected to a second-stage selective oxidation treatment with trivalent iron. In the second-stage treatment, an ORP sensor is used with a silver / silver chloride electrode as a reference electrode to monitor the oxidation-reduction potential in real time, selectively oxidizing and dissolving the remaining base metals while avoiding the loss of gold, resulting in gold-containing residue and base metal-containing waste liquid. S2, Acidic thiourea complex leaching: The gold-containing residue is added to acidic thiourea-Fe... 3+ The leaching system continuously monitors and replenishes thiourea during the leaching process to maintain its concentration stability, controls the leaching temperature, stirring rate and leaching time, and filters to obtain gold-containing leachate and leaching residue. S3. Functionalized composite adsorbent adsorption: The gold-containing leachate is passed into an adsorption column filled with a three-dimensional porous composite aerogel adsorbent material of functionalized graphene / chitosan / mesoporous silica. Graphene provides π electrons that interact specifically with gold, the amino and hydroxyl groups of chitosan provide chelating coordination active sites, and mesoporous silica provides high specific surface area mass transfer channels. The three work together to achieve selective and efficient adsorption of gold ions. S4. Elution: The adsorption column after adsorption saturation was eluted with acidic thiourea eluent to obtain a high-concentration gold-containing eluent. S5. Ultrasonic-assisted pulsed electrodeposition: The gold-containing eluent is subjected to pulsed electrodeposition using a pulsed power supply. An ultrasonic field is applied during the deposition process to promote mass transfer on the cathode surface and inhibit dendrite growth, thereby obtaining a dense and uniform gold deposit. After washing and drying, sponge gold is obtained. S6. Adsorbent regeneration and resource utilization: The adsorbent material that has been saturated with adsorption is eluted with acidic thiourea solution to remove residual gold ions, washed with deionized water until neutral, dried and reused; the leaching residue is dried and utilized as a resource. S7. Waste liquid classification and recycling: Waste liquid generated from the pretreatment, leaching, elution and electrodeposition steps is classified, collected and treated to recover valuable metal ions, and the treated water is returned to the corresponding process for recycling.

[0010] Furthermore, the conditions for the first-stage dilute sulfuric acid pre-soaking treatment in step S1 are: sulfuric acid concentration 0.5~2.0 mol / L, liquid-solid ratio 5:1~15:1 mL / g, pre-soaking temperature 20~50℃, and pre-soaking time 15~60 min; the conditions for the second-stage selective oxidation treatment of ferric iron are: ferric iron concentration 1~10 g / L, oxidation-reduction potential controlled at 300~500 mV (relative to the silver / silver chloride reference electrode), oxidation temperature 30~60℃, and oxidation time 30~120 min; the replenishment rate of ferric iron is adjusted by real-time feedback from the ORP sensor to stably control the oxidation-reduction potential within the set range.

[0011] Furthermore, the pulverization in step S1 is carried out under nitrogen or argon protection, with a particle size of 0.1~2 mm, and a 40~200 mesh screen is used for vibrating screening; the secondary selective oxidation treatment of ferric iron also includes ultrasonic-assisted enhancement, with an ultrasonic power of 200~600 W and an ultrasonic frequency of 20~50 kHz. The ultrasonic cavitation effect promotes the oxidation and dissolution of base metals and exposes the encapsulated gold-containing particles, thereby increasing the gold exposure rate in the subsequent leaching step.

[0012] Furthermore, the acidic thiourea-Fe described in step S2 3+ The leaching system consists of: sulfuric acid concentration of 0.3–1.5 mol / L, thiourea concentration of 8–30 g / L, and ferric iron concentration of 2–10 g / L. The leaching process also includes microwave-assisted enhancement, with a microwave power of 300–800 W and a frequency of 2450 MHz. The selective heating effect of microwaves creates localized hot spots on the surface of gold-containing particles, accelerating the gold dissolution reaction. Continuous monitoring and replenishment of thiourea involves online thiourea concentration detection. When thiourea consumption reaches a set lower threshold, thiourea is automatically replenished to a set upper threshold to ensure that the thiourea concentration in the leaching system remains within an effective range, inhibiting Fe2+ dissolution. 3+ Excessive oxidative decomposition of thiourea.

[0013] Furthermore, the functionalized graphene / chitosan / mesoporous silica three-dimensional porous composite aerogel adsorbent material described in step S3 is prepared by the following method: first, mesoporous silica nanoparticles are mixed evenly with carboxylated graphene dispersion, then chitosan acetate solution and crosslinking agent epichlorohydrin are added, and the crosslinking reaction is carried out at 40~70℃ for 3~6 h. After forming a gel, it is freeze-dried to obtain the three-dimensional porous composite aerogel; wherein, the mass ratio of carboxylated graphene to chitosan is 1:1~1:5, and the amount of mesoporous silica added is 10%~50% of the total mass of carboxylated graphene and chitosan.

[0014] Furthermore, the mesoporous silicon has a pore size of 5-20 nm and a specific surface area of ​​200-600 m². 2 / g, with an average particle size of 50~200 nm; the adsorption column has a packing height of 15~50 cm, an adsorption temperature of 20~40℃, and an adsorption flow rate of 0.5~3 mL / min.

[0015] Furthermore, in the acidic thiourea eluent described in step S4, the thiourea concentration is 50~100 g / L, the sulfuric acid concentration is 0.5~2 mol / L, the elution temperature is 50~80℃, and the elution flow rate is 0.5~2 mL / min.

[0016] Furthermore, the parameters for pulse electrodeposition in step S5 are: pulse frequency 100~400 Hz, duty cycle 30%~50%, and average current density 8~20 mA / cm². 2 The electrodeposition time is 3-6 h; the ultrasonic power of the ultrasonic-assisted method is 100-300 W, and the ultrasonic frequency is 20-50 kHz; before the pulse electrodeposition, the gold-containing eluent is pre-electrolyzed to remove residual base metal impurities, and the pre-electrolysis current density is 2-5 mA / cm². 2 The pre-electrolysis time is 0.5~1 h.

[0017] Furthermore, the regeneration rate of the adsorbent material in step S6 is not less than 95%; the waste liquid treatment in step S7 adopts ion exchange resin adsorption or membrane separation technology, wherein the pretreated waste liquid is treated to recover base metal ions such as copper and zinc, the leaching waste liquid is recovered and purified by thiourea and returned to the leaching process, the elution waste liquid is concentrated and returned to the elution process, and the electrodeposition waste liquid is purified and returned to the electrodeposition process; the temperature, stirring rate, oxidation-reduction potential and feeding rate in the pretreatment and leaching processes are automatically adjusted by the PLC control system, and the ORP control accuracy is ±10 mV.

[0018] Furthermore, the purity of the sponge gold recovered through the aforementioned process is not less than 99.5%, and the total gold recovery rate is not less than 80%.

[0019] The beneficial effects of this technical solution are: (1) The multi-stage selective oxidation pretreatment technology achieves highly selective separation of base metals and gold: the first-stage dilute sulfuric acid pre-leaching treatment mainly removes active base metals such as copper and zinc with high content in the mixed powder by controlling the sulfuric acid concentration and liquid-solid ratio, avoiding the competitive interference of base metals on gold leaching when directly thiourea leaching; the second-stage trivalent iron selective oxidation treatment utilizes Fe 3+ / Fe 2+ Taking advantage of the standard electrode potential falling between that of base metals and gold, a silver / silver chloride electrode is used as a reference electrode to monitor the redox potential in real time. The replenishment rate of ferric iron is adjusted through real-time feedback from the ORP sensor, stabilizing the redox potential within the range of 300–500 mV, thus ensuring the Fe... 3+It selectively oxidizes and dissolves residual base metals such as copper and nickel, while gold, due to its much higher electrode potential than Fe, is more efficient. 3+ The base metals remain intact in the solid residue. Through the synergistic effect of primary pre-leaching and secondary selective oxidation, the total removal rate of base metals can reach over 95%, creating extremely favorable conditions for subsequent efficient adsorption and recovery.

[0020] (2) Online thiourea concentration monitoring and automatic replenishment technology achieved stable control of the leaching process: in acidic thiourea-Fe 3+ In the leaching system, thiourea forms a stable complex cation with gold [Au(SC(NH2)2)2]. + At the same time, Fe 3+ It can also oxidize and decompose thiourea to produce byproducts such as dimethylaminodithioformamide, leading to increased thiourea consumption. This invention uses online thiourea concentration detection to monitor changes in thiourea concentration in the leaching system in real time; when the thiourea concentration is consumed to a set lower threshold, an automatic replenishment system is activated to replenish thiourea to the set upper limit, ensuring that the thiourea concentration in the leaching system is always maintained within the effective range of 8~30 g / L, effectively inhibiting Fe... 3+ Excessive oxidative decomposition of thiourea maintains the stability of the thermodynamic driving force and gold leaching efficiency of the leaching system. Compared with the traditional method of adding thiourea all at once, the consumption of thiourea can be reduced by 20-30%, and the gold leaching rate can be increased by 5-10%.

[0021] (3) Functionalized graphene / chitosan / mesoporous silica three-dimensional porous composite aerogel adsorption technology achieves efficient enrichment and highly selective adsorption of gold ions: This composite aerogel organically combines the high specific surface area and π-electron specificity of carboxylated graphene, the strong coordination chelating ability of chitosan's amino and hydroxyl groups, and the high porosity and large specific surface area mass transfer channels of mesoporous silica to form a composite material with a three-dimensional interconnected pore network structure. The synergistic mechanism of the three components is as follows: the conjugated π-electron system of carboxylated graphene interacts specifically with gold ions, while providing a large specific surface area and conductive channels; the -NH2 and -OH groups in the chitosan molecule complex the gold thiourea cation [Au(SC(NH2)2)2] + Strong coordination chelation occurs; the nanopores of mesoporous silica provide a high specific surface area and molecular sieving effect, promoting the mass transfer and diffusion of gold ions. Simultaneously, its surface silanol groups can form hydrogen bonds with chitosan, enhancing the material's structural stability. This composite aerogel exhibits a saturated adsorption capacity of 500–800 mg / g for gold ions, far exceeding that of traditional activated carbon adsorbents (approximately 50–100 mg / g). Due to the synergistic effect of the triple selective adsorption sites, it can effectively adsorb gold ions even in environments containing Cu. 2+ Ni 2+ Fe 3+In complex leachates containing competing metal ions, gold can achieve selective adsorption rates of over 95%, elution rates of over 95%, and regeneration rates of over 95%.

[0022] (4) Ultrasonic-assisted pulsed electrodeposition technology enables efficient recovery of high-purity sponge gold: Before pulsed electrodeposition, the gold-containing eluent is pre-electrolyzed to remove any trace base metal impurities (such as copper and nickel). The pre-electrolysis current density is controlled at 2~5 mA / cm². 2 The pre-electrolysis time is 0.5–1 h, allowing base metals to preferentially precipitate at lower current densities, resulting in a purer gold-containing eluent. Pulse electrodeposition uses a periodically on-off pulsed power supply. Compared to traditional DC electrodeposition, during the "on" phase of the pulse, gold ions are reduced and deposited at the cathode, while during the "off" phase, gold ions in the bulk solution diffuse to the cathode surface to replenish it, effectively avoiding dendritic growth and loose deposition layers caused by concentration polarization. An ultrasonic field is applied during deposition; the ultrasonic cavitation effect promotes bubble desorption at the cathode surface, improving boundary layer mass transfer and resulting in a denser and more uniform gold deposition layer. Through pulse parameter optimization and ultrasonic synergy, the purity of the obtained sponge gold can reach over 99.5%, and the density index (tap density) is more than 20% better than that of DC electrodeposition products.

[0023] (5) Waste liquid classification, recycling, and intelligent control technology realize green and clean production: the pretreated waste liquid contains Cu 2 + Ni 2+ Zn 2+ Valuable metal ions are selectively adsorbed and recovered using ion exchange resin (D401 chelating resin), and the purified liquid can be reused in the pretreatment step. Leaching wastewater undergoes vacuum distillation to recover thiourea, followed by deep treatment using a combination of ultrafiltration and reverse osmosis membranes; the permeate is reused in leaching agent preparation. Elution wastewater is concentrated and returned to the elution step for recycling. Electrodeposition wastewater is purified and returned to the electrodeposition process. Through wastewater classification, separate treatment, and tiered reuse, water consumption is reduced by over 60%, thiourea consumption by over 25%, and metal ion recovery rate is increased by over 10%. Key parameters such as oxidation-reduction potential (ORP using a silver / silver chloride reference electrode), pH, and temperature are monitored in real-time by online sensors, and the data is transmitted to the PLC control system, enabling automated and precise control of the pretreatment and leaching processes. The ORP control accuracy reaches ±10 mV, ensuring process stability and product consistency. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the preparation process for a gold recycling process from waste circuit boards proposed in this invention. Detailed Implementation

[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] Example 1:

[0027] (1) Multi-stage selective oxidation pretreatment Pre-treatment stage: Take 100 kg of waste circuit boards, remove the surface plastic packaging shell and solder and other impurities, crush them to a particle size of about 2 mm using a jaw crusher under nitrogen protection, remove ferromagnetic metals by magnetic separation, and then pass them through a 100-mesh vibrating sieve (corresponding to a particle size of 0.15 mm) to obtain 8.5 kg of gold-enriched mixed powder. Let the mixed powder air dry naturally for later use.

[0028] Primary dilute sulfuric acid pre-leaching treatment: The above mixed powder is added to a pre-leaching reactor, and a dilute sulfuric acid pre-leaching solution is added, wherein the sulfuric acid concentration is 0.5 mol / L and the liquid-to-solid ratio is 10:1 mL / g. The pre-leaching temperature is controlled at 25℃, the mechanical stirring rate is 200 r / min, and the pre-leaching time is 30 min. During the reaction, active base metals such as copper and zinc react with dilute sulfuric acid to form corresponding sulfates that enter the solution. After the reaction is completed, vacuum filtration is performed, and the filter residue is washed twice with deionized water to obtain the primary treated filter residue.

[0029] Determination of base metal removal rate: 0.5 g (accurate to 0.0001 g) of solid samples before and after pre-leaching were digested with aqua regia (concentrated hydrochloric acid to concentrated nitric acid, volume ratio 3:1). The digestate was diluted to a 100 mL volumetric flask and then further diluted to the mark with deionized water. 10 mL of the filtrate sample after pre-leaching was diluted to a 100 mL volume with 1% dilute nitric acid. The concentrations of Cu and Zn in the solution were determined using atomic absorption spectrometry, and the base metal removal rate was calculated. The results showed that the copper removal rate was 52% and the zinc removal rate was 78% after the first-stage pre-leaching treatment.

[0030] Secondary selective oxidation treatment of ferric iron: The filter residue from the primary treatment was added to the selective oxidation reactor, followed by a ferric iron-sulfuric acid selective oxidation solution. The sulfuric acid concentration was 0.1 mol / L, and the ferric iron concentration was 1 g / L (prepared from ferric sulfate, analytical grade). The online ORP monitoring system (silver / silver chloride reference electrode) was activated, and the redox potential was controlled at 320 mV (relative to the silver / silver chloride reference electrode), with an ORP control accuracy of ±10 mV. The oxidation temperature was controlled at 35℃, the mechanical stirring rate at 180 r / min, and the oxidation time at 60 min. During the reaction, Fe... 3+It selectively oxidizes and dissolves residual base metals such as copper and nickel, while gold, due to its much higher electrode potential than Fe, is more efficient. 3+ The gold was retained in the solid. After the reaction was completed, the mixture was vacuum filtered, and the filter residue was washed three times with deionized water to obtain gold-containing residue.

[0031] Determination of base metal removal rate: 0.5 g of solid samples before and after secondary treatment were taken, and the Cu and Ni contents were determined by aqua regia digestion-ICP-OES method; the Cu and Ni concentrations were determined by ICP-OES of the filtrate sample after secondary treatment. The results showed that the secondary selective oxidation treatment achieved a copper removal rate of 78% and a nickel removal rate of 82%. Combining the primary and secondary treatments, the total base metal removal rates were: copper 92%, zinc 78%, and nickel 82%.

[0032] (2) Acidic thiourea complex leaching The gold-containing residue was added to a leaching container, and acidic thiourea-Fe was added. 3+ The leaching system consisted of 0.3 mol / L sulfuric acid (analytical grade), an initial thiourea concentration of 10 g / L (analytical grade), and 2 g / L ferric iron, with a liquid-to-solid ratio of 10:1 mL / g. An online thiourea concentration monitoring system (using UV spectrophotometry) was activated, with a lower limit threshold of 6 g / L and an upper limit threshold of 12 g / L. The leaching temperature was controlled at 35℃, the stirring rate at 200 r / min, and the leaching time at 2 h. Online monitoring showed that the thiourea concentration dropped to 7.5 g / L after 60 min of leaching, triggering automatic replenishment to bring the concentration to 10 g / L. (The text then abruptly shifts to a discussion of thiourea and gold in Fe...) 3+ A stable complex cation [Au(SC(NH2)2)2] is formed under oxidation. + Gold dissolves from the solid residue into the solution. After leaching, the solution is filtered to obtain a gold-containing leachate and leaching residue.

[0033] Determination of gold leaching rate: Take 0.5 g of solid samples before and after leaching (accurate to 0.0001 g), and treat them using the aqua regia digestion method: add 10 mL of aqua regia, heat on a hot plate to digest to near dryness, repeat digestion twice, dissolve the residue with 1% dilute nitric acid and dilute to a 50 mL volumetric flask. Determine the gold content using inductively coupled plasma mass spectrometry (ICP-MS). The gold leaching rate is calculated using the formula: Gold leaching rate = (Gold content in leaching solution / Gold content in sample before leaching) × 100%. Results: The gold leaching rate is 82%.

[0034] Determination of thiourea consumption: The total amount of thiourea added during the entire leaching process was recorded, and the thiourea consumption per unit of gold leaching was calculated. The results showed that when the gold leaching rate was 82%, the thiourea consumption was 3.2 kg / ton of waste circuit board, which was significantly lower than the 4.5 kg / ton of waste circuit board for the traditional one-time addition method.

[0035] (3) Adsorption of functionalized graphene / chitosan / mesoporous silica composite aerogel Preparation of adsorbent materials: Mesoporous silica nanoparticles (pore size 8 nm, specific surface area 350 m²) were used. 2 / g, average particle size 100nm) and carboxylated graphene dispersion (sheet diameter 2 μm, specific surface area 200 m²) 2 Carboxylated graphene (5 mg / mL) was mixed in deionized water at a mass ratio of 1:3 and ultrasonically dispersed for 30 min. Chitosan acetate solution (chitosan deacetylation degree ≥90%, molecular weight approximately 200,000, concentration 10 mg / mL) was added to make the mass ratio of carboxylated graphene to chitosan 1:3. Epichlorohydrin (analytical grade) was added as a crosslinking agent, with an addition amount 1.8 times the mass of chitosan. The crosslinking reaction was stirred at 55℃ for 4 h. After forming a gel, the gel was washed with deionized water until neutral and then freeze-dried (freezing temperature -50℃, drying time 24 h) to obtain a functionalized graphene / chitosan / mesoporous silica three-dimensional porous composite aerogel adsorbent material.

[0036] Material characterization: Scanning electron microscopy (SEM) was used to observe the morphology of the material, revealing a three-dimensional interconnected pore network structure with uniform pore size distribution (50–500 nm); the specific surface area was measured using a Beta-Tact (BET) analyzer, and the specific surface area was 420 m². 2 / g, total pore volume is 1.8 cm³ 3 / g; X-ray photoelectron spectroscopy (XPS) was used to analyze the surface elemental composition to confirm the presence and bonding state of C, O, N, and Si elements; Fourier transform infrared spectroscopy (FTIR) was used to analyze the functional groups to confirm the presence of carboxyl, amino, and silanol groups.

[0037] Adsorption experiment: The gold-containing leachate was passed into an adsorption column (20 cm high, 5 cm diameter) filled with the composite aerogel adsorbent material at a flow rate of 1.5 mL / min, and the adsorption temperature was controlled at 25℃. Gold ions were efficiently adsorbed by the adsorbent material.

[0038] Determination of adsorption capacity and breakthrough curve: The breakthrough curve was determined using an intermittent sampling method. Every 30 minutes, 1 mL of sample was taken from the adsorption column outlet and diluted to 10 mL with 1% dilute nitric acid. The gold ion concentration in the effluent was determined by ICP-MS. The breakthrough point was defined as when the gold ion concentration in the effluent reached 10% of the inlet concentration. The breakthrough adsorption capacity was calculated based on the integral of the breakthrough curve. Results: The adsorption breakthrough capacity was 520 mg / g.

[0039] Selective adsorption experiment: Under the same conditions, a competitive ion adsorption experiment was conducted on Cu in the leachate. 2+ Concentration 50 mg / L, Ni 2+Concentration 20 mg / L, Fe 3+ The concentration was 10 mg / L. After adsorption saturation, the adsorption capacities of Au, Cu, Ni, and Fe on the adsorbent material were determined by aqua regia digestion-ICP-MS. The results showed that the adsorption capacity of gold was 520 mg / g, copper was 12 mg / g, nickel was 5 mg / g, and iron was 3 mg / g. The selective adsorption rate of gold (relative to the total adsorption capacity) was 96.8%. (4) Washing The adsorption column was eluted with an acidic thiourea eluent. The concentration of thiourea in the eluent was 60 g / L, the concentration of sulfuric acid was 0.8 mol / L, the elution temperature was 55℃, and the elution flow rate was 0.8 mL / min. After elution, a high-concentration gold-containing eluent was obtained.

[0040] Determination of gold elution rate: The eluent was collected, and the gold content in the eluent was determined by aqua regia digestion-ICP-MS method. The gold elution rate was calculated as follows: Gold elution rate = (Gold content in eluent / Total amount of gold adsorbed by the adsorbent material) × 100%. Results: The gold elution rate was 95%.

[0041] (5) Ultrasonic-assisted pulse electrodeposition Pre-electrolysis treatment: The gold-containing eluent obtained in step (4) is transferred to a pre-electrolysis cell, with a stainless steel mesh as the anode and a stainless steel plate as the cathode, and the pre-electrolysis current density is controlled at 3 mA / cm². 2 The pre-electrolysis time was 45 min. During the pre-electrolysis process, trace base metal impurities (copper, nickel, etc.) preferentially precipitated at a lower current density, while gold remained in the solution. After the pre-electrolysis was completed, the precipitates were removed by filtration, yielding a purified gold-containing eluent.

[0042] Pulse electrodeposition: A pulsed power supply was used with a stainless steel plate (100 mm × 50 mm × 1 mm) as the cathode and a graphite rod as the anode to perform pulse electrodeposition on the purified gold-containing eluent. Ultrasonic assistance was performed simultaneously with the pulse electrodeposition. Ultrasonic assistance parameters were: ultrasonic power 150 W, ultrasonic frequency 28 kHz. Pulse parameters were set as follows: pulse frequency 150 Hz, duty cycle 35%, average current density 10 mA / cm². 2 The electrodeposition time was 5 hours. Gold was reduced and deposited at the cathode to obtain a gold deposit. After electrodeposition, the cathode was removed, the surface of the gold deposit was thoroughly washed with deionized water, dried, and scraped to obtain the sponge gold product.

[0043] Determination of sponge gold purity: Take 0.1 g of sponge gold sample (accurate to 0.0001 g), dissolve it in 5 mL of aqua regia, heat on a hot plate to evaporate to near dryness, repeat the process twice, dissolve the residue with 1% dilute nitric acid and dilute to 100 mL in a volumetric flask. Determine the gold content using ICP-MS and calculate the sponge gold purity. Gold purity = (mass of gold in sample / total mass of sample) × 100%. Results: The purity of sponge gold is 99.5%.

[0044] Morphology analysis of sponge gold: The surface morphology of sponge gold was observed using scanning electron microscopy (SEM). The results showed that the sponge gold obtained by pulse + ultrasound co-deposition exhibited a dense and uniform granular accumulation structure with no obvious dendritic growth and good surface smoothness.

[0045] Gold recovery rate determination: A full-process material balance method was used. 100 kg of waste circuit board raw material and the final product, sponge gold, were weighed separately. The gold recovery rate was calculated as: (mass of gold in sponge gold / mass of gold in waste circuit board) × 100%. Considering the losses in each step of pretreatment, leaching, adsorption, elution, and electrodeposition, the gold recovery rate was determined to be 72%.

[0046] (6) Adsorbent regeneration and resource utilization The saturated adsorbent was regenerated by elution with an acidic thiourea solution (60 g / L thiourea, 0.8 mol / L sulfuric acid) at a temperature of 55°C and a flow rate of 0.8 mL / min until the gold concentration in the eluent was below 1 mg / L. The adsorbent was then washed with deionized water until neutral, dried, and reused.

[0047] Determination of adsorbent regeneration rate: 0.2 g of regenerated adsorbent material was packed into a small adsorption column, and a gold-containing solution of known concentration (Au 50 mg / L) was passed through it. Adsorption experiments were conducted at a flow rate of 1.5 mL / min. The concentration of the effluent was determined using ICP-MS, and the regenerated adsorption capacity was calculated. Regeneration rate = (Regenerated adsorption capacity / Initial adsorption capacity) × 100%. Results: The regenerated adsorption capacity was 93% of the initial capacity.

[0048] After the leachate residue obtained in step (2) is naturally dried, it is ground into powder and mixed with cement and sand in a mass ratio of 1:3:6 to prepare a building filler sample. The sample was tested and found to meet the relevant building material standards (GB / T 14684-2011).

[0049] (7) Waste liquid is classified and recycled. Pretreatment of waste liquid: The waste liquid generated from the primary dilute sulfuric acid pre-leaching treatment is collected and sent to an ion exchange system (D401 chelating resin column) to adsorb and recover Cu. 2+ Zn 2+Low-grade metal ions; the purified solution is reused in the primary pre-soaking step.

[0050] Leaching waste liquid: After collecting the waste liquid generated in the thiourea complex leaching step, it is first subjected to vacuum distillation (temperature 60~80℃, vacuum degree 0.08~0.09 MPa) to recover thiourea. The distillation condensate is reused in the leaching step. The distillation residue is treated by a combination of ultrafiltration and reverse osmosis membrane process, and the product water is reused in the preparation of leaching agent.

[0051] Elution waste liquid: The waste liquid generated in the elution step is collected and concentrated under reduced pressure (temperature 50~70℃). The concentrate is then reused in the elution step.

[0052] Electrodeposition waste liquid: The waste liquid generated in the electrodeposition step is collected, purified (pH adjustment + precipitation and filtration), and then reused in the electrodeposition process.

[0053] Water consumption and thiourea consumption determination: In Example 1, after adopting the waste liquid recycling system, the water consumption was 3.5 tons / ton of waste circuit board (compared to about 8.5 tons / ton of waste circuit board in the traditional process), a reduction of 59%; the thiourea consumption was 3.2 kg / ton of waste circuit board (compared to about 4.5 kg / ton of waste circuit board in the traditional process), a reduction of 29%.

[0054] Example 2:

[0055] (1) Multi-stage selective oxidation pretreatment Pre-treatment stage: Take 100 kg of waste circuit board, remove the plastic packaging shell and solder and other impurities from the surface, crush it to a particle size of about 1 mm using a jaw crusher under nitrogen protection, remove ferromagnetic metals by magnetic separation, and then pass it through an 80-mesh vibrating sieve (corresponding to a particle size of 0.18 mm) to obtain 8.5 kg of gold-enriched mixed powder, which is then naturally dried for later use.

[0056] Primary dilute sulfuric acid pre-impregnation treatment: The above mixed powder was added to a pre-impregnation reactor, and a dilute sulfuric acid pre-impregnation solution was added, wherein the sulfuric acid concentration was 1.2 mol / L and the liquid-to-solid ratio was 12:1 mL / g. The pre-impregnation temperature was controlled at 40℃, the mechanical stirring rate was 250 r / min, and the pre-impregnation time was 45 min. After the reaction was completed, vacuum filtration was performed, and the filter residue was washed twice with deionized water to obtain the primary treated filter residue.

[0057] Secondary selective oxidation treatment of ferric iron (ultrasound-assisted): The filter residue after primary treatment was added to a selective oxidation reactor equipped with an ultrasonic probe, and a ferric iron-sulfuric acid selective oxidation solution was added, wherein the sulfuric acid concentration was 0.2 mol / L and the ferric iron concentration was 5 g / L. Ultrasonic assistance was activated at a power of 400 W and a frequency of 28 kHz. The ORP online monitoring system (silver / silver chloride reference electrode) was activated, and the oxidation-reduction potential was controlled at 420 mV with an ORP control accuracy of ±10 mV. The oxidation temperature was controlled at 50℃, the mechanical stirring rate at 200 r / min, and the oxidation time at 90 min. After the reaction, vacuum filtration was performed, and the filter residue was washed three times with deionized water to obtain gold-containing residue.

[0058] Determination of base metal removal rate: The concentrations of Cu, Ni, and Zn in the solution before and after pretreatment were determined by ICP-OES. Results showed that the primary pre-immersion treatment achieved a copper removal rate of 65% and a zinc removal rate of 85%; the secondary selective oxidation treatment (ultrasound-assisted) achieved a copper removal rate of 88% and a nickel removal rate of 90%. Combining the primary and secondary treatments, the total base metal removal rates were: copper 96%, zinc 85%, and nickel 90%.

[0059] (2) Acidic thiourea complex leaching The gold-containing residue was added to a leaching container equipped with a microwave reactor, and acidic thiourea-Fe was added. 3+ The leaching system consisted of 0.8 mol / L sulfuric acid (analytical grade), an initial thiourea concentration of 18 g / L (analytical grade), and 6 g / L ferric iron (prepared from ferric sulfate), with a liquid-to-solid ratio of 12:1 mL / g. Microwave assistance was used at 500 W and 2450 MHz. An online thiourea concentration monitoring system was activated, with a lower threshold of 10 g / L and an upper threshold of 20 g / L. The leaching temperature was controlled at 50℃, the mechanical stirring rate at 220 r / min, and the leaching time at 2 h. The thiourea concentration dropped to 11.5 g / L after 80 min, triggering automatic replenishment to 18 g / L. The solution was filtered to obtain a gold-containing leaching solution and leaching residue.

[0060] Determination of gold leaching rate: 0.5 g of solid samples were taken before and after leaching, and the samples were processed using aqua regia digestion-ICP-MS method. The gold content was determined by ICP-MS. Results: The gold leaching rate was 90%.

[0061] (3) Adsorption of functionalized graphene / chitosan / mesoporous silica composite aerogel Preparation of adsorbent material: Mesoporous silica nanoparticles (pore size 12 nm, specific surface area 450 m²) were used. 2 / g, average particle size 150 nm) and carboxylated graphene dispersion (particle size 3 μm, specific surface area 280 m²) 2The graphene (5 mg / mL) was mixed in deionized water at a mass ratio of 1:2 and ultrasonically dispersed for 30 min. Chitosan acetate solution was added to make the mass ratio of carboxylated graphene to chitosan 1:2. Epichlorohydrin, a crosslinking agent, was added, with the amount added being 1.6 times the mass of chitosan. The crosslinking reaction was carried out at 60℃ for 3.5 h. After forming a gel, the gel was washed with deionized water until neutral and then freeze-dried to obtain a functionalized graphene / chitosan / mesoporous silica three-dimensional porous composite aerogel adsorbent material.

[0062] Adsorption experiment: The gold-containing leachate was passed into an adsorption column (30 cm high, 5 cm in diameter) filled with the composite aerogel adsorbent material at a flow rate of 2 mL / min, and the adsorption temperature was controlled at 30℃. Gold ions were efficiently adsorbed by the adsorbent material.

[0063] Determination of adsorption capacity and selective adsorption: An intermittent sampling method was used, with samples taken from the adsorption column outlet every 20 minutes. The concentration of gold ions in the effluent was determined by ICP-MS. Results: The adsorption breakthrough capacity was 680 mg / g. Selectivity was determined using the same method as in Example 1, with a gold selective adsorption rate of 97.2%.

[0064] (4) Washing The adsorption column was eluted with an acidic thiourea eluent. The concentration of thiourea in the eluent was 80 g / L, the concentration of sulfuric acid was 1.2 mol / L, the elution temperature was 65℃, and the elution flow rate was 1.2 mL / min. After elution, a high-concentration gold-containing eluent was obtained.

[0065] Determination of gold elution rate: The gold content in the eluent was determined by aqua regia digestion-ICP-MS method. Results: The gold elution rate was 97%.

[0066] (5) Ultrasonic-assisted pulse electrodeposition Pre-electrolysis treatment: using stainless steel mesh as the anode and stainless steel plate as the cathode, the pre-electrolysis current density is controlled at 4 mA / cm². 2 The pre-electrolysis time was 30 min. The precipitate was removed by filtration to obtain the purified gold-containing eluent.

[0067] Pulse electrodeposition: A pulsed power supply was used with a stainless steel plate (100 mm × 50 mm × 1 mm) as the cathode and a graphite rod as the anode to perform pulse electrodeposition on the purified gold-containing eluent. Ultrasonic assistance was performed simultaneously with the pulse electrodeposition. Ultrasonic assistance parameters were: ultrasonic power 200 W, ultrasonic frequency 28 kHz. Pulse parameters were set as follows: pulse frequency 200 Hz, duty cycle 40%, average current density 15 mA / cm². 2The electrodeposition time was 4 hours. Gold was reduced and deposited at the cathode to obtain a gold deposit. After electrodeposition, the cathode was removed, the surface of the gold deposit was thoroughly washed with deionized water, dried, and scraped to obtain the sponge gold product.

[0068] Determination of sponge gold purity: 0.1 g of sponge gold sample was dissolved in aqua regia, and the gold content was determined by ICP-MS. Results: The purity of the sponge gold was 99.7%.

[0069] Morphology analysis of sponge gold: SEM observation showed that the sponge gold obtained by pulse + ultrasound co-deposition had a very dense and uniform granular stacked structure with a very smooth surface and no dendritic growth. Its density was better than that of Example 1.

[0070] Gold recovery rate determination: The entire process material balance method was used. Results: The gold recovery rate was 78%.

[0071] (6) Adsorbent regeneration and resource utilization The adsorbent material that has reached adsorption saturation is regenerated by elution with an acidic thiourea solution (thiourea 80 g / L, sulfuric acid 1.2 mol / L), at an elution temperature of 65℃ and an elution flow rate of 1.2 mL / min. Elution continues until the gold concentration in the outlet eluent is less than 1 mg / L. The eluent is then washed with deionized water until neutral, dried, and reused.

[0072] Determination of adsorbent regeneration rate: Adsorption experiments were conducted on the regenerated adsorbent material to determine the regenerated adsorption capacity. Results: The regeneration rate was 96%.

[0073] The leaching residue is used to prepare building fillers.

[0074] (7) Waste liquid is classified and recycled. The waste liquid classification and recycling system was operated in the same way as in Example 1. The results showed that the water consumption was 3.2 tons / ton of waste circuit board and the thiourea consumption was 2.8 kg / ton of waste circuit board.

[0075] Example 3:

[0076] (1) Multi-stage selective oxidation pretreatment Pre-treatment stage: Take 100 kg of waste circuit board, remove the plastic packaging shell and solder and other impurities from the surface, crush it to a particle size of about 0.5 mm using a jaw crusher under nitrogen protection, remove ferromagnetic metals by magnetic separation, and then pass it through a 120 mesh vibrating sieve (corresponding to a particle size of 0.12 mm) to obtain 8.5 kg of gold-enriched mixed powder, which is then air-dried for later use.

[0077] Primary dilute sulfuric acid pre-impregnation treatment: The above mixed powder was added to a pre-impregnation reactor, and a dilute sulfuric acid pre-impregnation solution was added, wherein the sulfuric acid concentration was 2.0 mol / L and the liquid-to-solid ratio was 15:1 mL / g. The pre-impregnation temperature was controlled at 50℃, the mechanical stirring rate was 300 r / min, and the pre-impregnation time was 60 min. After the reaction was completed, vacuum filtration was performed, and the filter residue was washed twice with deionized water to obtain the primary treated filter residue.

[0078] Secondary selective oxidation treatment of ferric iron (ultrasound-assisted enhancement): The filter residue after primary treatment was added to a selective oxidation reactor equipped with an ultrasonic probe, along with a ferric iron-sulfuric acid selective oxidation solution, wherein the sulfuric acid concentration was 0.3 mol / L and the ferric iron concentration was 10 g / L. Ultrasonic assistance was activated at a power of 600 W and a frequency of 40 kHz. An online ORP monitoring system (silver / silver chloride reference electrode) was activated, controlling the oxidation-reduction potential at 480 mV with an ORP control accuracy of ±10 mV. The oxidation temperature was controlled at 60℃, the mechanical stirring rate at 250 r / min, and the oxidation time at 120 min. After the reaction, vacuum filtration was performed, and the filter residue was washed three times with deionized water to obtain gold-containing residue.

[0079] Determination of base metal removal rate: The concentrations of Cu, Ni, and Zn in the solution before and after pretreatment were determined by ICP-OES. Results showed that the primary pre-immersion treatment achieved a copper removal rate of 75%, a zinc removal rate of 92%, and a nickel removal rate of 45%; the secondary selective oxidation treatment achieved a copper removal rate of 95% and a nickel removal rate of 96%. Combining the primary and secondary treatments, the total base metal removal rates were: copper 99%, zinc 92%, and nickel 98%.

[0080] (2) Acidic thiourea complex leaching The gold-containing residue was added to a leaching container equipped with a microwave reactor, and acidic thiourea-Fe was added. 3+ The leaching system consisted of 1.5 mol / L sulfuric acid (analytical grade), an initial thiourea concentration of 30 g / L (analytical grade), and 10 g / L ferric iron (prepared from ferric sulfate), with a liquid-to-solid ratio of 15:1 mL / g. Microwave assistance was used at 800 W and 2450 MHz. An online thiourea concentration monitoring system was activated, with a lower threshold of 20 g / L and an upper threshold of 30 g / L. The leaching temperature was controlled at 60℃, the mechanical stirring rate at 280 r / min, and the leaching time at 3 h. The solution was filtered to obtain a gold-containing leaching solution and leaching residue.

[0081] Determination of gold leaching rate: 0.5 g of solid samples were taken before and after leaching, and the gold content was determined by aqua regia digestion-ICP-MS method. Results: The gold leaching rate was 95%.

[0082] (3) Adsorption of functionalized graphene / chitosan / mesoporous silica composite aerogel Preparation of adsorbent material: Mesoporous silica nanoparticles (pore size 18 nm, specific surface area 550 m²) were used. 2 / g, average particle size 180 nm) and carboxylated graphene dispersion (sheet diameter 4 μm, specific surface area 350 m²) 2 The graphene (5 mg / mL) was mixed in deionized water at a mass ratio of 1:1 and ultrasonically dispersed for 30 min. Chitosan acetate solution was added to make the mass ratio of carboxylated graphene to chitosan 1:1. Epichlorohydrin, a crosslinking agent, was added, with the amount added being 1.5 times the mass of chitosan. The crosslinking reaction was carried out at 70℃ for 2.5 h. After the gel was formed, it was washed with deionized water until neutral and then freeze-dried to obtain a functionalized graphene / chitosan / mesoporous silica three-dimensional porous composite aerogel adsorbent material.

[0083] Adsorption experiment: The gold-containing leachate was passed into an adsorption column (45 cm high, 5 cm in diameter) filled with the composite aerogel adsorbent material at a flow rate of 3 mL / min, and the adsorption temperature was controlled at 40℃. Gold ions were efficiently adsorbed by the adsorbent material.

[0084] Determination of adsorption capacity and selective adsorption: An intermittent sampling method was used, with samples taken from the adsorption column outlet every 15 min. The concentration of gold ions in the effluent was determined by ICP-MS. Results: The adsorption breakthrough capacity was 780 mg / g. Selectivity was determined using the same method as described above, with a gold selective adsorption rate of 98.1%.

[0085] (4) Washing The adsorption column was eluted with an acidic thiourea eluent. The concentration of thiourea in the eluent was 100 g / L, the concentration of sulfuric acid was 2 mol / L, the elution temperature was 80℃, and the elution flow rate was 2 mL / min. After elution, a high-concentration gold-containing eluent was obtained.

[0086] Determination of gold elution rate: The eluent was collected, and the gold content was determined by aqua regia digestion-ICP-MS. Results: The gold elution rate was 99%.

[0087] (5) Ultrasonic-assisted pulse electrodeposition Pre-electrolysis treatment: using stainless steel mesh as the anode and stainless steel plate as the cathode, the pre-electrolysis current density is controlled at 5 mA / cm². 2 The pre-electrolysis time was 30 min. The precipitate was removed by filtration to obtain the purified gold-containing eluent.

[0088] Pulse electrodeposition: A pulsed power supply was used with a titanium plate (100 mm × 50 mm × 1 mm) as the cathode and a graphite rod as the anode to perform pulse electrodeposition on the purified gold-containing eluent. Ultrasonic assistance was performed simultaneously with the pulse electrodeposition. The ultrasonic assistance parameters were: ultrasonic power 300 W, ultrasonic frequency 40 kHz. The pulse parameters were set as follows: pulse frequency 300 Hz, duty cycle 45%, and average current density 20 mA / cm². 2 The electrodeposition time was 3 hours. Gold was reduced and deposited at the cathode to obtain a gold deposit. After electrodeposition, the cathode was removed, the surface of the gold deposit was thoroughly washed with deionized water, dried, and scraped to obtain the sponge gold product.

[0089] Determination of sponge gold purity: 0.1 g of sponge gold sample was dissolved in aqua regia, and the gold content was determined by ICP-MS. Results: The purity of the sponge gold was 99.9%.

[0090] Morphology analysis of sponge gold: SEM observation shows that the sponge gold obtained by pulse + ultrasound synergistic enhanced deposition has an extremely dense and uniform spherical stacked structure, without any dendritic growth, and the surface is very smooth with optimal density.

[0091] Gold recovery rate determination: The entire process material balance method was used. Results: The gold recovery rate was 82%.

[0092] (6) Adsorbent regeneration and resource utilization Regeneration of saturated adsorbents: Elution and regeneration were performed using an acidic thiourea solution (100 g / L thiourea, 2 mol / L sulfuric acid) at a temperature of 80°C and a flow rate of 2 mL / min. Elution continued until the gold concentration in the eluent was below 1 mg / L. The eluent was then washed with deionized water until neutral, dried, and reused.

[0093] Determination of adsorbent regeneration rate: Regenerated adsorption capacity / Initial adsorption capacity × 100%. Result: Regeneration rate was 98%.

[0094] The leaching residue is used to prepare building fillers.

[0095] (7) Waste liquid is classified and recycled. The waste liquid classification and recycling system was operated in the same way as in Example 1. The results showed that the water consumption was 2.8 tons / ton of waste circuit board and the thiourea consumption was 2.5 kg / ton of waste circuit board.

[0096] Comparative Example 1: This comparative example is based on Example 2, except that the first-stage dilute sulfuric acid pre-soaking treatment in the multi-stage selective oxidation pretreatment is omitted, and only the second-stage trivalent iron selective oxidation treatment is performed. The remaining parameters are the same as in Example 2.

[0097] Comparative Example 2: This comparative example is based on Example 2, except that the functionalized graphene / chitosan / mesoporous silica three-dimensional porous composite aerogel adsorbent is replaced with traditional coconut shell activated carbon adsorbent, while the other parameters are the same as in Example 2.

[0098] Comparative Example 3: This comparative example is based on Example 2, except that pulse electrodeposition is replaced with conventional DC electrodeposition, and the other parameters are the same as in Example 2.

[0099] Comparative Example 4: This comparative example is based on Example 2, except that the online thiourea concentration monitoring and automatic replenishment system is removed, and the traditional one-time addition of thiourea is adopted. All other parameters are the same as in Example 2.

[0100] Comparative Example 5: This comparative example is based on Example 2, except that the pre-electrolysis treatment step is omitted, while the other parameters are the same as in Example 2.

[0101] The test results of the various embodiments and comparative examples of the present invention are as follows: As can be seen from the data in the table above, there are significant differences between the embodiments of the present invention and the comparative examples in various key performance indicators, which verifies the necessity and effectiveness of core technologies such as multi-stage selective oxidation pretreatment, online thiourea monitoring and replenishment, adsorption of functionalized graphene / chitosan / mesoporous silica composite aerogel, and synergistic pre-electrolysis treatment and pulse electrodeposition.

[0102] In Comparative Example 1 (without primary pre-immersion treatment), the total removal rate of base metals was only 75% / 68% / 85%, and the gold leaching rate was 68%, far lower than the 96% / 90% / 85% and 90% of Example 2. This is because base metals (Cu, Ni, Zn) compete with gold to consume thiourea and Fe. 3 + The oxidation reaction of base metals consumes a large amount of Fe. 3+ This reduces the effective Fe used in gold oxide 3+ The amount of thiourea consumed was as high as 4.2 kg / ton. Meanwhile, after base metal ions entered the leachate, they competed with gold ions for adsorption sites in subsequent adsorption steps, causing the adsorption capacity to decrease from 680 mg / g to 420 mg / g. Ultimately, the gold recovery rate decreased from 78% to 55%, only 71% of that in Example 2.

[0103] The gold adsorption capacity of Comparative Example 2 (conventional activated carbon adsorption) was only 95 mg / g, far lower than the 680 mg / g of Example 2, a decrease of 86%. The activated carbon adsorbed 15% of the copper and 8% of the nickel, indicating that it also has strong adsorption of base metals, but poor selectivity. The gold selective adsorption rate was only 78.2%, far lower than the 97.2% of Example 2. The final gold purity of the sponge was only 98.1%, lower than the 99.7% of Example 2. The overall gold recovery rate decreased from 78% to 52%, only 67% of that of Example 2.

[0104] The gold purity of Comparative Example 3 (DC electrodeposition) was 99.0%, lower than that of Example 2 (99.7%). The gold deposit obtained by DC electrodeposition exhibited slight dendritic growth and poor surface smoothness. DC electrodeposition required 6 hours to achieve a similar deposition thickness, while pulsed electrodeposition only required 4 hours, and the gold recovery rate of pulsed electrodeposition (78%) was slightly higher than that of DC electrodeposition (76%).

[0105] The gold leaching rate of Comparative Example 4 (without online thiourea monitoring and replenishment) was 85%, lower than the 90% of Example 2, a decrease of 6%. This is because the traditional one-time addition of thiourea results in thiourea in the Fe... 3+ Under oxidation, the gold gradually decomposes, and insufficient thiourea concentration in the later stages of leaching leads to a decrease in gold leaching efficiency. The thiourea consumption is as high as 4.5 kg / ton, far exceeding the 2.8 kg / ton in Example 2. The final gold recovery rate is 70%, lower than the 78% in Example 2.

[0106] The gold sponge from Comparative Example 5 (without pre-electrolysis treatment) had a purity of 99.2%, lower than the 99.7% of Example 2. This is because the eluent may contain trace amounts of base metal impurities (such as copper and nickel), which are partially trapped in the gold deposition layer during the electrodeposition process, affecting purity. Pre-electrolysis treatment removes these impurities, ensuring the purity of the final product.

[0107] Example 1: Gold leaching rate 82%, thiourea consumption 3.2 kg / ton, adsorption capacity 520 mg / g, gold recovery rate 72%; Example 2 shows a good balance between the following indicators: gold leaching rate of 90%, thiourea consumption of 2.8 kg / ton, adsorption capacity of 680 mg / g, and gold recovery rate of 78%. Example 3 showed the best technical indicators: gold leaching rate of 95%, thiourea consumption of 2.5 kg / ton, adsorption capacity of 780 mg / g, and gold recovery rate of 82%.

[0108] Example 2 employs a combination of multi-stage selective oxidation pretreatment, online thiourea monitoring and replenishment, composite functionalized adsorbent, pulse + ultrasound synergistic electrodeposition + pre-electrolysis treatment, which ensures high recovery rate while having good economic efficiency and operability, and has the best overall cost performance.

[0109] Comparison results between various embodiments of the present invention and waste liquid recycling: In Embodiment 3 of this invention, after adopting a waste liquid recycling system, water consumption was reduced by 67%, copper recovery rate was 95%, nickel recovery rate was 88%, and gold recovery rate was 84%, achieving significant economic and environmental benefits.

[0110] The sources of the key reagents and materials used in this invention are summarized as follows: The above descriptions are merely embodiments of the present invention, and common knowledge regarding specific technical solutions or characteristics is not elaborated upon here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. A gold recovery process from waste circuit boards, characterized in that, Includes the following steps: S1. Multi-stage selective oxidation pretreatment: Remove the plastic packaging shell and impurities from the waste circuit board, crush it under inert gas protection, remove iron powder by magnetic separation, and obtain a gold-enriched mixed powder by vibrating sieve; first, the mixed powder is subjected to a first-stage dilute sulfuric acid pre-immersion treatment to remove most of the base metals, and then a second-stage selective oxidation treatment of trivalent iron is performed. In the second-stage treatment, an ORP sensor is used with a silver / silver chloride electrode as a reference electrode to monitor the oxidation-reduction potential in real time, and the residual base metals are selectively oxidized and dissolved to obtain gold-containing residue and base metal-containing waste liquid; S2, Acidic thiourea complex leaching: The gold-containing residue is added to acidic thiourea-Fe... 3+ The leaching system continuously monitors and replenishes thiourea during the leaching process to maintain its concentration stability, controls the leaching temperature, stirring rate and leaching time, and filters to obtain gold-containing leachate and leaching residue. S3. Functionalized composite adsorbent adsorption: The gold-containing leachate is passed into an adsorption column filled with a three-dimensional porous composite aerogel adsorbent material of functionalized graphene / chitosan / mesoporous silica. The three work together to achieve selective and efficient adsorption of gold ions. S4. Elution: The adsorption column after adsorption saturation was eluted with acidic thiourea eluent to obtain a high-concentration gold-containing eluent. S5. Ultrasonic-assisted pulsed electrodeposition: The gold-containing eluent is subjected to pulsed electrodeposition using a pulsed power supply. An ultrasonic field is applied during the deposition process to promote mass transfer on the cathode surface and inhibit dendrite growth, thereby obtaining a dense and uniform gold deposit. After washing and drying, sponge gold is obtained. S6. Adsorbent regeneration and resource utilization: The adsorbent material that is saturated with adsorption is eluted with acidic thiourea solution to remove residual gold ions, washed with deionized water until neutral, and dried for reuse. S7. Waste liquid classification and recycling: Waste liquid generated from the pretreatment, leaching, elution and electrodeposition steps is classified, collected and treated to recover valuable metal ions, and the treated water is returned to the corresponding process for recycling.

2. The gold recovery process from waste circuit boards according to claim 1, characterized in that, The conditions for the primary dilute sulfuric acid pre-soaking treatment in step S1 are: sulfuric acid concentration 0.5~2.0 mol / L, liquid-solid ratio 5:1~15:1 mL / g, pre-soaking temperature 20~50℃, and pre-soaking time 15~60 min; the conditions for the secondary selective oxidation treatment with ferric iron are: ferric iron concentration 1~10 g / L, oxidation-reduction potential controlled at 300~500 mV, oxidation temperature 30~60℃, and oxidation time 30~120 min.

3. The gold recovery process from waste circuit boards according to claim 1, characterized in that, The pulverization in step S1 is carried out under nitrogen or argon protection, the pulverization particle size is 0.1~2 mm, and the vibrating screen is a 40~200 mesh screen; the secondary selective oxidation treatment of ferric iron also includes ultrasonic-assisted enhancement, with an ultrasonic power of 200~600 W and an ultrasonic frequency of 20~50 kHz.

4. The gold recovery process from waste circuit boards according to claim 1, characterized in that, The acidic thiourea-Fe in step S2 3+ The leaching system consists of: sulfuric acid concentration of 0.3~1.5 mol / L, thiourea concentration of 8~30 g / L, and ferric iron concentration of 2~10 g / L. The leaching process also includes microwave-assisted enhancement with a microwave power of 300~800 W and a frequency of 2450 MHz. The continuous monitoring and replenishment of thiourea is achieved by automatically replenishing thiourea to the set upper limit when the thiourea is consumed to a set lower limit threshold through online thiourea concentration detection.

5. The gold recovery process from waste circuit boards according to claim 1, characterized in that, The functionalized graphene / chitosan / mesoporous silica three-dimensional porous composite aerogel adsorbent material described in step S3 is prepared by the following method: first, mesoporous silica nanoparticles are mixed evenly with carboxylated graphene dispersion, then chitosan acetate solution and crosslinking agent epichlorohydrin are added, and the crosslinking reaction is carried out at 40~70℃ for 3~6 h. After forming a gel, it is freeze-dried to obtain the three-dimensional porous composite aerogel; wherein, the mass ratio of carboxylated graphene to chitosan is 1:1~1:5, and the amount of mesoporous silica added is 10%~50% of the total mass of carboxylated graphene and chitosan.

6. The gold recovery process from waste circuit boards according to claim 5, characterized in that, The mesoporous silicon has a pore size of 5-20 nm and a specific surface area of ​​200-600 m². 2 / g, with an average particle size of 50~200 nm; the adsorption column has a packing height of 15~50 cm, an adsorption temperature of 20~40℃, and an adsorption flow rate of 0.5~3 mL / min.

7. The gold recovery process from waste circuit boards according to claim 1, characterized in that, In step S4, the acidic thiourea eluent has a thiourea concentration of 50-100 g / L, a sulfuric acid concentration of 0.5-2 mol / L, an elution temperature of 50-80℃, and an elution flow rate of 0.5-2 mL / min.

8. The gold recovery process from waste circuit boards according to claim 1, characterized in that, The parameters for pulse electrodeposition in step S5 are: pulse frequency 100~400 Hz, duty cycle 30%~50%, and average current density 8~20 mA / cm². 2 The electrodeposition time is 3-6 h; the ultrasonic power of the ultrasonic-assisted method is 100-300 W, and the ultrasonic frequency is 20-50 kHz; before the pulse electrodeposition, the gold-containing eluent is pre-electrolyzed to remove residual base metal impurities, and the pre-electrolysis current density is 2-5 mA / cm². 2 The pre-electrolysis time is 0.5~1 h.

9. The gold recovery process from waste circuit boards according to claim 1, characterized in that, The regeneration rate of the adsorbent material in step S6 is not less than 95%; the waste liquid treatment in step S7 adopts ion exchange resin adsorption or membrane separation technology, wherein the pre-treated waste liquid recovers base metal ions such as copper and zinc after treatment, the leaching waste liquid is returned to the leaching process after thiourea recovery and purification, the elution waste liquid is returned to the elution process after concentration, and the electrodeposition waste liquid is returned to the electrodeposition process after purification; the temperature, stirring rate, oxidation-reduction potential and feeding rate in the pre-treatment and leaching processes are automatically adjusted by the PLC control system, and the ORP control accuracy is ±10 mV.

10. The gold recovery process from waste circuit boards according to any one of claims 1 to 9, characterized in that, The gold obtained by the process described above has a purity of not less than 99.5% and a total gold recovery rate of not less than 80%.

Citation Information

Patent Citations

  • A kind of carboxymethyl chitosan / graphene oxide composite hydrogel and its preparation and application

    CN105622960B

  • Methods for separating valuable and base metals in circuit boards

    CN107841630B

  • Composite graphene chitosan aerogel and preparation method and application thereof

    CN112473630A

  • Method for preferentially stripping gold-plated layer of waste circuit board based on controlled potential erosion method

    CN119265418A

  • Preparation method and application of reduced graphene oxide composite aerogel material

    CN121103267A